Bariatric surgery: a clinical case report of laparoscopic longitudinal gastric resection in a patient with morbid obesity and gastrointestinal stromal tumor of the stomach - Evgeniy N. Degovtsov; Pavel V. Kolyadko; Vasily P. Kolyadko; Vladimir S. Samoylov; Artem V. Stepanenko; Aleksey V. Satinov (LLC "MEDIAFORMAT", 2022)
Gastrointestinal stromal tumor (GIST) is the most common tumor of the submucosal layer of the gastrointestinal tract. With the development of diagnostic methods, the incidence of GIST cases has increased significantly. Similarly, the prevalence of morbid obesity has increased significantly in the last decade. It is known from the literature that the incidence of GIST in obese patients is higher than in the general population. Although marginal and sparing resection is the first treatment for GIST, depending on the size and location of the tumor, broader surgery should also be considered. Laparoscopic sleeve gastrectomy is one of the most popular bariatric procedures. It can also be an option for concomitant treatment of both morbid obesity and gastric GIST when the tumor is within the range of sleeve resection.